AB2 polymerization on hollow microporous organic polymers: engineering of solid acid catalysts for the synthesis of soluble cellulose derivatives. Issue 4 (13th January 2020) - Chae, Su Kyung; Cho, Kyoungil; Lee, Sang Moon; Kim, Hae Jin; Ko, Yoon-Joo; Son, Seung Uk
Abstract : New post-synthetic functionalization of hollow microporous organic polymers was developed based on AB2 polymerization and thiol–yne click reaction. Abstract : This work shows a new post-synthetic strategy of a microporous organic polymer (MOP) based on AB2 polymerization chemistry (polymerization of AB2 -type monomers). Hollow MOP (H-MOP) platforms were prepared by template synthesis via Sonogashira coupling of 1, 4-dibromo-2, 5-diethynylbenzene. The amount of terminal alkynes in the H-MOP was amplified via AB2 polymerization. Through the thiol–yne click reaction, aliphatic sulfonic acids were incorporated into the terminal alkyne-enriched H-MOP. The resultant solid acid catalysts showed efficient performance in the synthesis of soluble cellulose derivatives.